Learning Video Making Training In Pangkep Regency South Sulawesi - Retyana Wahrini; Hasbi (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2023)
In mid-2019 all countries in the world faced the Covid-19 pandemic caused by the Corona virus. Until now, in early 2022, this pandemic has not yet found a cure and is even continuing to expand and more and more people are infected with this virus. The outbreak of this virus caused the Indonesian government to impose large-scale social restrictions (PSBB) and restrictions on community activities (PKM) level 3, level 2 and level 1 for areas affected by this disease, including the city of Makassar. One of the impacts of imposing restrictions in the world of education is causing schools and campuses to implement online learning or learning from home. Based on these conditions, designing and preparing the learning process involves many components and activities that must be well planned, systematic and measurable using internet technology and interactive applications. However, most of the teachers who teach in education units in elementary schools in Pangkajene and the Islands districts are still experiencing problems in preparing learning tools, especially audio-visual media which can be an alternative in delivering teaching material. Conditions like this have the potential to be used as a target location for community service activities in terms of training in making learning videos with screen recording applications. In addition, teachers in general already have laptops and even schools in general have personal computers, so understanding of computer operation is very good. Considering the many benefits, community service activities are carried out at SD Negeri 25 Taraweang, Labakkang District, Pangkep Regency, effective for 2 (two) months.